Pengaruh Drill Berbasis Media Audio Visual Terhadap Peningkatan Keterampilan Jurus Tunggal Atlet Pencak Silat Satria Muda Indonesia Kota Bekasi - Erin, Erin Desyaningrum; Haqiyah , Aridhotul (Motion: Journal Research of Physical Education, 2025)
This study aimed to examine the effect of drill training using audio-visual media on improving single-form skills in pencak silat athletes of Satria Muda Indonesia, Bekasi. A one-group pretest-posttest design was employed with 20 athletes as participants. The assessment instrument was based on IPSI standards. Results of the paired t-test showed significant improvement in all performance aspects, including technical accuracy, power, rhythm, and movement coordination (p < 0.05). Audio-visual media-based training proved effective as a visual and kinesthetic learning strategy in martial arts skill acquisition. This study contributes to training innovation in martial arts through the integration of digital media.